CNS Francis McNaughton Memorial Prize: Blood hemoglobin concentration as a potential predictor of outcomes after acute ischemic stroke. (3rd June 2015) - Furlan, JC; Fang, J; Silver, FL
Abstract : Background: This study examines whether abnormal blood hemoglobin concentration (bHB) is associated with worse clinical outcomes and poorer prognosis after acute ischemic stroke. Methods: We included data from the Registry of the Canadian Stroke Network on consecutive patients with ischemic stroke who were admitted between July/2003 and March/2008. Patients were divided into groups as follows: low bHB, normal bHB, and high bHB. Primary outcome measures were the frequency of moderate/severe strokes on admission (Canadian Neurological Scale: <8), greater degree of disability at discharge (modified Rankin score: 3-6), and 30-day and 90-day mortality. Results: Higher bHB than the superior normal limit is associated with greater degree of impairment (OR=1.45, 95%CI: 1.06-1.95, p=0.0195) and disability (OR=1.49, 95%CI: 1.03-2.15, p=0.0331), and higher 30-day mortality (HR=1.98, 95%CI: 1.44-2.74, p<0.0001) after adjustment for major potential confounders. The Kaplan-Meier curves indicate that abnormal bHB is associated with higher mortality after acute ischemic stroke (p<0.0001). Lower bHB than the inferior normal limit is associated with longer stay in the acute stroke care center (OR=1.11, 95%CI: 1.02-1.22, p=0.017). Conclusions: Polycythemia on the initial admission is associated with poorer prognosis regarding the degree of impairment and disability, and 30-day mortality after an acute ischemic stroke. Anemia on admission is associated with longer stay in the acute stroke center.